2019
DOI: 10.3390/molecules24132430
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Expanded Snack of Rice Starch Enriched with Amaranth by Extrusion Process

Abstract: This study aimed to obtain a second-generation snack by extrusion from the by-product of rice milling enriched with amaranth. The raw material used was amaranth flour (AF), rice starch (NS) and modified rice starch (MS), which were evaluated by the analysis of substitution degree (SD), differential scanning calorimetry (DSC), viscosity (RVA), Fourier transform infrared spectroscopy (FT-IR) and X-ray diffraction (XRD). The snacks were expanded by extrusion and microwave oven, as a reference method. The samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 56 publications
1
14
0
1
Order By: Relevance
“…Hardness (maximum force for breaking the sample) significantly decreased with the increase in RB content compared with control (P < 0.05) (Table 3). Similar results were reported for extruded products enriched with amaranth (Diaz et al, 2013;Castellanos-Gallo et al, 2019), kañiwa or quinoa (Diaz et al, 2013), long-chain inulin (Peressini et al, 2015) and shiitake mushroom (Lu et al, 2020). On the contrary, other works reported that inclusion of wheat bran in extruded cereal products (Brennan et al, 2008) and oat bran in corn starch-based extrudate increased hardness (Lobato et al, 2011).…”
Section: Physical Propertiessupporting
confidence: 78%
See 1 more Smart Citation
“…Hardness (maximum force for breaking the sample) significantly decreased with the increase in RB content compared with control (P < 0.05) (Table 3). Similar results were reported for extruded products enriched with amaranth (Diaz et al, 2013;Castellanos-Gallo et al, 2019), kañiwa or quinoa (Diaz et al, 2013), long-chain inulin (Peressini et al, 2015) and shiitake mushroom (Lu et al, 2020). On the contrary, other works reported that inclusion of wheat bran in extruded cereal products (Brennan et al, 2008) and oat bran in corn starch-based extrudate increased hardness (Lobato et al, 2011).…”
Section: Physical Propertiessupporting
confidence: 78%
“…Hardness is the result of interactions between components (Diaz et al, 2013). Reduction in hardness could be due to: a) fibre limited interactions between polysaccharide (and proteins) (Diaz et al, 2013;Castellanos-Gallo et al, 2019); b) low adhesion between starch and bran particles at their interface (Robin et al, 2011). For starch-based extrudates containing bran, microscopy observations of cell walls clearly showed two distinctive phases (gelatinised Mean AE standard deviation (n = 3).…”
Section: Physical Propertiesmentioning
confidence: 99%
“…It can be explained by the source of the starch and its conditions before modification, since the starch is diluted and does not allow the greater substitution of acetyl groups because there is not enough availability of hydroxyls susceptible to this substitution. In a study by Castellanos-Gallo et al [ 17 ], they analyzed the effect of acetylation on rheological properties in rice starch. They found similar value in a degree of substitution (0.05) and percentage of acetylation (1.43) to that obtained in this work and to the study performed by Colussi et al [ 16 ] mentioned above, in which a methodology carried out with similar conditions and concentrations in starch was used.…”
Section: Resultsmentioning
confidence: 99%
“…The intermediate products, also known as pellets, are obtained from a mixture of various ingredients, starches being one of the most common. During frying, the pellets expand to give the crisps their specific structure [ 1 ]. Frying is among the most widespread forms of food processing.…”
Section: Introductionmentioning
confidence: 99%